Analisis Pengendalian Kualitas Produk Plastik Menggunakan Metode DMAIC Pada PT Techpack Asia - Syafiq Tian Maulana (Journal of Engineering and Applied Technology, 2026)
This study investigates the mitigation of cosmetic spot defects on premium polymer cosmetics packaging caused by airborne particulate contamination at PT Techpack Asia using the DMAIC framework. Structured empirical field observations utilizing a calibrated particle counter across twenty seven strategic nodes isolated material entry hatches as the primary vectors of microdust infiltration due to electrostatic charges. The implementation of high frequency housekeeping protocols alongside predictive mechanical rejuvenation successfully reduced particulate concentrations of 1 micron and 5 micron dimensions well below the World Health Organization (2021) maximum thresholds. Statistical validation through control charts in the final phase established a proactive detection mechanism that prevents microclimatic variance from disrupting the injection molding and decoration sequences. The structured quality architecture achieved a significant reduction in visual scrap rates down to 0.4 percent in the compliant zones. Ultimately this research demonstrates that integrating environmental cleanroom parameters into statistical quality control charts ensures high process predictability and permanent visual quality stabilization for premium plastic manufacturing operations.